Taxonomy and Phylogeny of the Dileptid Ciliate Genus Paradileptus (Protista: Ciliophora), With a Brief Review and Redescriptions of Two Species Isolated From a Wetland in Northern China - Chi, Yong; Wang, Zhe; Lu, Borong; Ma, Honggang; Mu, Changjun; Warren, Alan; Zhao, Yan (Frontiers in Microbiology, 2021)
Members of the genus Paradileptus are apex predators in microbial food webs. They are often encountered in freshwater biotopes and have been used in the research of water quality monitoring and ecology. Nevertheless, our understanding of the biodiversity of Paradileptus, especially its ecological and genetic diversities, is very poor which hinders our ability to understand the ecosystem services it provides. The present study gives a detailed account of two Chinese populations of Paradileptus elephantinus and P. conicus including their living morphology, infraciliature, and molecular phylogenies based on 18S, 5.8S, and ITS ribosomal DNA sequences. The phylogenetic relationships between these two species and other rhynchostomatians are investigated. We also explore the potential contribution of differentiation of the proboscis (e.g., extrusomes, dorsal brush, and differentiated kineties) to niche partitioning and speciation in Paradileptus. The global distribution of Paradileptus is summarized based on published data. Finally, a key to the identification of the valid species of Paradileptus is provided.